Hand Function and Quality of Life in Children with Epidermolysis Bullosa. Issue 2 (26th November 2013) - Eismann, Emily A.; Lucky, Anne W.; Cornwall, Roger
Abstract Patient‐reported outcomes are becoming increasingly important to clinical care. Epidermolysis bullosa (EB), a rare genetic skin disorder, can result in severe hand impairment, but parent and patient perceptions of hand function have never been assessed. This study aimed to quantify parent‐ and patient‐reported hand function and assess its relationship with quality of life (QOL) in children with EB. This cross‐sectional study included children with EB treated at an interdisciplinary EB center. Hospital records were searched for demographic characteristics and medical history. Eligible families were invited to complete two surveys by mail or telephone. The ABILHAND‐Kids questionnaire assessed manual hand ability for 21 functions. The Quality of Life in Epidermolysis Bullosa questionnaire assessed EB‐related QOL. Hand function and QOL of various subtypes were compared using Mann–Whitney tests. Seventy‐one parents and patients ages 2 to 18 years with EB from 20 states in the United States completed questionnaires. Children with recessive dystrophic EB reported the worst hand function and QOL. Bimanual functions involving finger mobility were the most challenging for all EB subtypes. QOL was highly related to the degree of hand function, being correlated with 20 of the 21 individual hand functions and most associated with the ability to perform unimanual functions. Parent‐ and patient‐reported hand function can be measured in children with EB using the ABILHAND‐Kids questionnaire. Hand impairment is strongly associated with worse QOL, probably due to difficulty performing daily activities. The effect of interventions such as hand surgery could be prospectively evaluated using this questionnaire.